The Application of Good Corporate Governance (GCG) Through the Implementation of Quality Management System at PT. CS - Rintis Sukma Dewi (Journal of Accounting and Finance Management, 2020)
Good corporate governance (GCG) is a system that organizes and controls a company to create value added to all stakeholders. Quality Management System ISO 9001:2015 is an approach done by the company in running business by maximizing the company competitiveness through improvement that is done continuously towards goods, services, resources, process, and environment. The descriptive research and literature research methods used in this article show that the implementation of quality management system at PT. CS could create a good corporate governance, viz could provide a more structured company management system so that it could produce better goods and services quality. The result of this research shows that GCG which the company applies through the implementation of quality management system is well materialized. The success of the implementation of quality management system could be proven by the customer trust towards the goods and services that the company produces. The rate of customer trust could influence the growth of the economy of the company so that the company goal to reach maximum profit could be reached and thus increasing the company accountability so that it gives long term value towards shareholders without neglecting other stakeholders’ interests.